2020
DOI: 10.25046/aj050481
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Mindset towards Self-Regulated Learning of Undergraduate Students at the University of Phayao

Abstract: The effects of Covid-19 severely affected the Thai higher education model. Therefore, there are three significant objectives in this research: (1) to cluster the mindsets and attitudes toward self-regulated learning styles of undergraduate students at the University of Phayao. (2) to construct a predictive model for recommending an appropriate student learning clusters. (3) to evaluate the predictive model that has been constructed. Samples collected a compilation of 472 student satisfaction with questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The researchers found that four students were at the risk of dropping out of the education system, which is expected to be affected by COVID-19. It is consistent with the many research studies (Casanova et al, 2021;de Oliveira et al, 2021;Karimi-Haghighi et al, 2022;Nuankaew, 2020;Nuankaew & Nuankaew, 2021;Viloria & Pineda Lezama, 2019), reflecting this research's importance that aims to develop a predictive model for clustering learning outcomes affected by COVID-19.…”
Section: Participation In Student Learning Activitiessupporting
confidence: 83%
See 1 more Smart Citation
“…The researchers found that four students were at the risk of dropping out of the education system, which is expected to be affected by COVID-19. It is consistent with the many research studies (Casanova et al, 2021;de Oliveira et al, 2021;Karimi-Haghighi et al, 2022;Nuankaew, 2020;Nuankaew & Nuankaew, 2021;Viloria & Pineda Lezama, 2019), reflecting this research's importance that aims to develop a predictive model for clustering learning outcomes affected by COVID-19.…”
Section: Participation In Student Learning Activitiessupporting
confidence: 83%
“…The tools used in the teaching and learning process need to rely on communication technology and Internet networks. In addition, learners' learning styles must be adapted to self-directed control and self-regulated learning theories to achieve expected outcomes (Kizilcec et al, 2017;Lim et al, 2020;Nuankaew, 2020). Instructor monitoring is achieved through the design of learning activities focused on practice rather than traditional lectures.…”
Section: Introductionmentioning
confidence: 99%
“…The research approaches are based on the theory of data mining development using the interprofessional standard process for data mining, known as the Cross-Industry Standard Process for Data Mining (CRISP-DM) methodology [22][23][24][25][26][27], which is widely accepted in data mining development. The research approach is divided into two sections.…”
Section: Research Approachesmentioning
confidence: 99%
“…The research conducted on the number of students in the University of Phayao shows the relevance of the number of students increasing every year (Nuankaew, 2020;Nuankaew et al, 2020;Phanniphong et al, 2018). At the same time, the number of studies, research, and development of technology to be applied for the benefit of the community is not reasonable.…”
Section: Methodsmentioning
confidence: 99%